Ozone Monitoring Instrument (OMI) collection 4: establishing a 17-year-long series of detrended level-1b data - Kleipool, Quintus; Rozemeijer, Nico. C.; Hoek, Mirna van; Leloux, Jonatan; Loots, Erwin; Ludwig, Antje; Plas, Emiel van der; Adrichem, Daley; Harel, Raoul; Spronk, Simon; Linden, Mark ter; Jaross, Glen; et al. (Atmospheric measurement techniques, 2022)
The Ozone Monitoring Instrument (OMI) was launched on 15 July 2004, with an expected mission lifetime of 5 years. After more than 17 years in orbit the instrument is still functioning satisfactorily and in principle can continue doing so until the expected decommissioning of its platform Aura in 2025. In order to continue the datasets acquired by OMI and the Microwave Limb Sounder, the mission was extended up to at least 2023. Actions have been taken to ensure the proper functioning of the OMI operations, the data processing, and the calibration monitoring system until the eventual end of the mission. For the data processing a new level-0 (L0) to level-1b (L1b) data processor was built based on the recent developments for the TROPOspheric Monitoring Instrument (TROPOMI). With corrections for the degradation of the instrument now included, it is feasible to generate a new data collection to supersede the current collection-3 data products and reprocess the data of the entire mission up to now. This paper describes the differences between the collection-3 and collection-4 data. It will be shown that the collection-4 L1b data comprise a clear improvement with respect to the previous collections. By correcting for the gentle optical and electronic aging that has occurred over the past 17 years, OMI’s ability to make trend-quality ozone measurements has further improved.